Fodder Trees and their Importance in India - Debboy, R.; Shankar Narayan, K. A.; Pathak, P. S. (Indian Forester, 1980)
In this paper the problem of sustenance of huge livestock population vis-a-vis this paucity of green nutritious fodder has been emphasized. The importance of fodder tree in suppling highly nutritious green fodder especially during the lean period and their specific role in the flood affected areas, arid and semi-arid region and also in hilly areas has been illustrated. Plantation of fodder tree their lopping management, nutritive value have been described.